Analisis Pengaruh Kualitas Produk Kosmetik Merek Temulawak - Lida Urbaningrum; Rosiyanti Rosiyanti; Syamsul Hidayat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Temulawak is a cosmetic brand in Indonesia. Temulawak cosmetic products must compete so that their flagship products are able to attract consumer buying interest and dominate market share. The aim of this research is to analyze the quality of ginger cosmetic products on the decision to purchase these products. The research was carried out by distributing questionnaires online via Google Form to 100 respondents as a sample. The collected primary data will be tested for validity and readability and then analyzed using multiple linear regression analysis and processed using SPSS version 26 software. The results of the research show that product quality has a positive effect on purchasing decisions. The research results provide implications for ginger cosmetic products to improve product quality. By implementing this strategy, it is hoped that consumer purchasing decisions for ginger cosmetic products can be improved.